Informed Play Approaching a Concept and Biology of Tone Production on Early Modern Lute Instruments - Rolfhamre , Robin (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
Informed Play presents a conceptual understanding of tone production based on extensive historical research on primary sources, modern literature and handbook reviews, physical and psychological perspectives as well as on technology. As the first volume in English to discuss and contextualise the topic of tone production on Early Modern lute instruments from a broad, interdisciplinary approach, it represents a unique and significant contribution to research on Early Music performance, particularly performance on lute instruments. At a lute-centred level, this book challenges many preconceptions about tone production by addressing the motivations behind certain choices made in and embraced by the Early Music community. It is therefore an essential 'desk reference' for both researchers and performers. At a meta-level, Informed Play offers a general perspective of how self-expressive acts, physical and social causes and effects can be perceived biologically to better understand historical music performance as a social practice and phenomenon.